(untitled) (International Journal of Management and Sustainability, 2020)
Organizations have long been concerned on how management can facilitate Organizational Citizenship Behavior (OCB) and employee engagement (EE) which can result in higher performance and productivity. This study attempted to test the mediating role of demographic attributes on the relationship between employee engagement and organizational citizenship behavior in the context of local enterprises in Dhaka city, Bangladesh. The authors administered 524 participants along with on employee engagement scale (5 factors) and organizational citizenship scale (5 factors). After the validation of the model only 3 factors from OCB and 4 factors from EE have been retained. The study finally reveals the Employee Engagement (EE) has a positively significant impact on OCB. However, in mediating effect the demographic attributes (Experience) partially mediates the relationship on OCB factors but do not mediate on EE. Rest of the mediating effect of gender and age were not supported the hypothesis.